The Effect of Regional Taxes and Regional Levies on Regional Original Income there is an Office of the Regional Financial and Asset Management Agency of Central Sulawesi Province - Rajindra; Wahba; Windy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
This study aims to determine the effect of regional taxes and regional levies on the original regional income of Central Sulawesi province. The research method used is Quantitative research method. The results of the study showed that regional taxes affected the original regional income of Central Sulawesi province simultaneously and partially. Similarly, the Regional Levy also affects the Regional Original Income of Central Sulawesi Province simultaneously and partially.